2021
DOI: 10.1080/22221751.2021.1914516
|View full text |Cite
|
Sign up to set email alerts
|

The genetic feature and virulence determinant of highly virulent community-associated MRSA ST338-SCCmec Vb in China

Abstract: ST59 is the predominant pathotype of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) in China. As a variant of ST59, there is relatively little known about the detailed information of ST338. To address this issue, here, we described thirteen ST338 CA-MRSA strains isolated from severe bloodstream infection cases, and focused on their epidemiology, genetic features and virulence potential. Phylogenetic analysis showed the earliest isolated strain of this study is likely a predecessor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…The most prevalent were the Asian-Pacific clone ST59-SCC mec IV ( n = 231, 30.84%) and the New York/Japan ST5-SCC mec II clone ( n = 154, 20.56%), followed by the ST239-SCC mec III ( n = 54, 7.21%) clone and the Panton-Valentine leucocidin (PVL)-positive Taiwan clone ST59-SCC mec V ( n = 34, 4.54%). Based on detailed clinical information, 10 ST59 clones from Zhejiang Province and 13 ST338 clones ( 25 ) were confirmed as CA-MRSA, while 73 ST5 clones and 2 ST239 clones from Zhejiang Province were confirmed to be HA-MRSA isolates. However, due to a lack of available clinical records, other strains could not be identified as CA-MRSA or HA-MRSA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent were the Asian-Pacific clone ST59-SCC mec IV ( n = 231, 30.84%) and the New York/Japan ST5-SCC mec II clone ( n = 154, 20.56%), followed by the ST239-SCC mec III ( n = 54, 7.21%) clone and the Panton-Valentine leucocidin (PVL)-positive Taiwan clone ST59-SCC mec V ( n = 34, 4.54%). Based on detailed clinical information, 10 ST59 clones from Zhejiang Province and 13 ST338 clones ( 25 ) were confirmed as CA-MRSA, while 73 ST5 clones and 2 ST239 clones from Zhejiang Province were confirmed to be HA-MRSA isolates. However, due to a lack of available clinical records, other strains could not be identified as CA-MRSA or HA-MRSA.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to types II and III, MRSA-IV and MRSA-V strains harbored smaller SCC mec elements ( 24 ). Previous study has demonstrated that smaller SCC mec cassettes may reduce the fitness burden ( 25 ). Therefore, the increase in ST59 MRSA-IV and MRSA-V clones may contribute to harboring a smaller SCC mec cassette, which lead to lower potential fitness burden.…”
Section: Discussionmentioning
confidence: 99%
“…More important CA-MRSA clones according to [ 2 , 23 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 ] are shown in Table 4 , most important HA-MRSA clones according to [ 23 , 85 , 125 , 220 , 224 , 233 , 234 , 235 , 236 ] are shown in Table 5 , and most important LA-MRSA clones according to [ 23 , 125 , 237 , 238 , 239 , 240 , 241 , 242 ] are shown in Table 6 .…”
Section: Molecular Epidemiology Of Mrsamentioning
confidence: 99%
“…The strain SO574/12 expresses a multidrug-resistance phenotype, highly similar to the previously described PM1 ST59-SCC mec V T /CC59 strain from Taiwan and the ZY05 ST338-SCC mec V T /CC59 strain from China [ 17 , 30 ]. Meanwhile, 13 ST338/CC59 strains among MRSA isolates obtained in China between 2014–2019, from human blood, were resistant only to erythromycin, clindamycin, and oxacillin [ 37 ]. The SO574/12 isolate is an older variant of ST338/CC59 CA-MRSA, but it appears more resistant than the more recent Chinese ones.…”
Section: Discussionmentioning
confidence: 99%
“…This may act as an excellent environment for the formation of ica ABCDR-dependent biofilm, a natural biological membrane. Due to the lack of the sdr D gene, the virulome of SO574/12 isolate (2012) shows similarity to ZY05 CA-MRSA (2016) but differs from the strains analyzed by Jin et al (2014–2019), which were described as negative in clf A, clf B, eap , cna , sdr C, sdr D, and ica D genes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%